Peran Media Sosial Sebagai Promosi Kesehatan Reproduksi Pada Remaja (Literature Review) - Novita Wulandari (Jurnal Kesehatan, 2025)
In Indonesia, one-fifth of the population is teenagers who are likely to engage in risky behaviour without being aware of the long-term consequences of such behaviour. They adopt risky behaviour through unhealthy relationships and undirected information. A global study concluded that the risks of using digital media are generally prominent for early adolescents; these risks include cyberbullying, online addiction, and sexting. The use of social media and insight into reproductive health can have an impact on risky sexual behaviour among adolescents. This study aims to highlight the importance of social media in promoting reproductive health in adolescents. The method used was a literature review. This research was obtained from the Stikes Ngesti Waluyo Health Journal and Google Scholar. The articles were published from 2018 to 2024 and sourced from various journals. This study consisted of seven articles that met two criteria: articles on the role of social media in health and articles published within the last six years. Based on the studies, the role of social media in health promotion for adolescents changes adolescent health in terms of maintaining and protecting reproductive health. With the increasingly sophisticated development of technology, the role of social media in reproductive health promotion is being used to disseminate information about the importance of reproductive health for adolescents. The conclusion is that social media has a vital role as a tool to support reproductive health in adolescents. Hence, through social media, adolescents in Indonesia will easily obtain more accurate, precise, and up-to-date information related to reproductive health.